Sustainable Supply Chain Management: A research into the Environmental and Social supply chain management for Sustainable Development - Godisela, Randhir (2010)
Motorola in collaboration with the University of Nottingham International Centre for Corporate Social Responsibility (ICCSR ) and Achilles Information Ltd, is conducting research into the business drivers and barriers around sharing Environmental, Social and Governance information within the supply chain. The literature integrates the concepts of corporate social responsibility and environmental management into the core supply chain management activities within the wider framework of sustainable development. The environmental and social challenges are researched since there is a growing recognition that development should go beyond economic growth. Whilst most research in the west has focused on the environmental approaches of supply chain management, this thesis seeks to understand, integrate, evaluate and find other options to better understand the business drivers and barriers. The methodological approach is structured to achieve the research objectives. The first and second primary studies confirm that suppliers‘ knowledge is inadequate in terms of establishing and publishing their environmental and social policies and procedures, such as implementing internal and external controls for suppliers. Their traditional and conservative mindsets are linked to their unwillingness to make a change despite the economic restructuring rapidly taking place. In particular, codes of conduct are commonly existing literature, embedded with environmental and social criteria as an important policy imposed by multinational buyers to improve both environmental and social conditions within the supply chain. But how effective are such policies? The key barriers have been identified as cost, lack of trust, lack of communication and training, and lack of knowledge. The key drivers are customer demands, cost and regulation. One of the main conclusion of the thesis is that the approach to the supply chain management is still evolving. A two way cooperation between the buyers and suppliers is fundamental to achieve a sustainable supply chain management.